Does Inward Foreign Direct Investment Boost the Productivity of Domestic Firms? - Haskel, Jonathan E; Pereira, Sonia C; Slaughter, Matthew J (The Review of Economics and Statistics, 2007)
Are there productivity spillovers from FDI to domestic firms, and, if so, how much should host countries be willing to pay to attract FDI? To examine these questions, we use a plant-level panel covering U.K. manufacturing from 1973 through 1992. Consistent with spillovers, we estimate a robust and significantly positive correlation between a domestic plant's TFP and the foreign-affiliate share of activity in that plant's industry. Typical estimates suggest that a 10-percentage-point increase in foreign presence in a U.K. industry raises the TFP of that industry's domestic plants by about 0.5%. We also use these estimates to calculate the per-job value of these spillovers at about £2,400 in 2000 prices ($4,300). These calculated values appear to be less than per-job incentives governments have granted in recent high-profile cases, in some cases several times less.